Frequency of Complications During Preparation of Corneal Lamellae Used in Posterior Lamellar Keratoplasty Using the Pneumodissection Technique (Big Bubble). Issue 7 (July 2018) - Studeny, Pavel; Netukova, Magdalena; Hlozanek, Martin; Bednar, Jan; Jirsova, Katerina; Krizova, Deli
Abstract : Purpose: To determine the frequency of formation of various types of bubbles and the potential impact of donor and lamella parameters on this frequency, and to identify possible risk factors of unsuccessful "big-bubble" creation in preparation of pre-Descemet endothelial keratoplasty and Descemet membrane endothelial keratoplasty with peripheral stromal support. Methods: Donor age and sex, death to preservation time (DPT), storage time, presence of corneal scars (mainly a condition after cataract surgery), and endothelial cell density of 256 donor corneas were assessed before Descemet membrane endothelial keratoplasty with peripheral stromal support or pre-Descemet endothelial keratoplasty lamella preparation using the big-bubble technique. Results: Mean donor age was 62.3 ± 8.5 years (28.3% women and 71.7% men). Mean endothelial cell density of the donor graft was 2866 ± 255 cells/mm 2 . Mean DPT was 10.12 ± 4.88 hours, and mean storage time of the transplant before surgery was 6.5 ± 4.8 days. Corneal scars were present in 17 donor grafts (6.6%) after cataract surgery. Eleven corneas were devalued because of Descemet membrane rupture during preparation (4.3%). In 182 corneas, standard bubble type I was created (71.7%); in 27 corneas, bubble type II was created; eventually, both types of bubbles formed simultaneously (10.5%); in 47 corneas, no bubble was created (18.4%). Conclusions: We identified higher endothelial cell density, shorter DPT, and the presence of corneal scars after cataract surgery as risk factors threatening successful bubble formation. The only risk factor for creating type II bubbles was higher donor age in our study.